A psicoterapia ontopsicológica: um mapeamento bibliográfico do período de 2007 a 2018 - Perin, Nathália (2018)
The term "Ontopsychology" emerge for the first time in Maslow's book, "Introduction to the Psychology of Being". From this work and with the influence of philosophy, psychoanalysis, Husserl's phenomenology and the existential-humanist current, Antonio Meneghetti develops Ontopsychology and one of its instruments, ontopsychological psychotherapy. Because this is a recent practice of the contemporary clinic and little diffused, this study aims to present the bibliographic production in Ontopsychology and the proposition of ontopsychological psychotherapy based on the work of Antonio Meneghetti and the other authors. The objective was to clarify not only the Ontopsychology, but more specifically the propositions of ontopsychological psychotherapy. For this, the method used was first a bibliographical review of the work of Antonio Meneghetti and later a bibliographic mapping characterized as state of the art of the other authors. This research aims to contribute to making this knowledge accessible, available even to other practices and lines of psychotherapy, also serving as support for new research and for the scientific community in general. As a quantitative result, in the bibliographic review of Meneghetti's work, in a universe of 92 books, 13 copies were selected, dating from 1989 to 2015. In the survey of the other authors' productions in Ontopsicologia, a total of 498 bibliographies produced between 2007 and 2018, among which Ontopsychology is cited, treated or as a paradigm or object of study. In this universe, 27 were selected on ontopsychological psychotherapy, equivalent to 5.4%. The qualitative results point out that Ontopsychology is an interdisciplinary epistemic science and presents three important findings: semantic field, deflection monitor and ontic Inself (its epistemic criterion). His vision of man conceives him as a unit of historical-spiritual action, which constitutes a terrestrial and also spiritual, ontic event. It has several instruments of intervention, among them the ontopsychological psychotherapy. It was identified by this research that ontopsychological psychotherapy, is characterized by its uniqueness of being an authentication psychotherapy. The term "authentic" is understood according to the capacity to be equal to how the being puts us. It enables man to increase his level of consciousness, to develop the capacity to recognize, among all the possibilities he has in life, those that are in conformity with his own essence. Another important field of research in Ontopsychology is the relationship between energy and image, and one of the premises is that psychic intentionality is formalized through images. The techniques of analysis and intervention are differentiated and allow to know the whole man, verifying if his psychic activity gives the ontological nexus